FACTORS AFFECTING USER SATISFACTION OF MOBILE JKN APPLICATION: A LITERATUR REVIEW - Luqyana Salsabila Anaqamy (Institute of Computer Science (IOCS), 2022)
Mobile JKN is a form of digital transformation launched by BPJS Kesehatan which aims to facilitate the service of the Jaminan Kesehatan Nasional-Kartu Indonesia Sehat. Considering the mandatory rule of JKN participation, there is a possibility for a higher demand in using Mobile JKN application in the future. However, based on the feedbacks for the Mobile JKN application on Playstore and Appstore as of December 28, 2021, it is known that the average rating is 3.4 out of 5 and 2.7 out of 5. This condition illustrates that there are still many users who are not satisfied with the application. This study aimed to identify the factors that affect the satisfaction of Mobile JKN users. This study was a literatur review using three databases including SAGE, Pubmed and Google Scholar. The inclusion criteria were the articles published in 2019-2021 and in full text. The result of this review showed there are various factors that are categorized into five dimensions; the reliability, tangibility, responsiveness, privacy, and assurance. And these dimensions affect the satisfaction of Mobile JKN application users.